Pathway of nitrous oxide consumption in isolated Pseudomonas stutzeri strains under anoxic and oxic conditions - Desloover, J.; Roobroeck, D.; Heylen, K.; Puig, S.; Boeckx, P.; Verstraeten, W.W.; Boon, N. (Wiley, 2014)
The microbial consumption of nitrous oxide (N2O) hasgained great interest since it was revealed that thisprocess could mitigate the greenhouse effect of N2O.The consumption of N2O results from its reduction todinitrogen gas (N2) as part of the denitrificationprocess. However, there is ongoing debate regardingan alternative pathway, namely reduction of N2OtoNH4+, or assimilatory N2O consumption. To date, thispathway is poorly investigated and lacks unambigu-ous evidence. Enrichment of denitrifying activatedsludge using a mineral nitrogen-free medium ren-dered a mixed culture capable of anoxic and oxicN2O consumption. Dilution plating, isolation anddeoxyribonucleic acid fingerprinting identified a col-lection ofPseudomonas stutzeristrains as dominantN2O consumers in both anaerobic and aerobic enrich-ments. A detailed isotope tracing experiment with aPseudomonas stutzeriisolate showed that consump-tion of N2O via assimilatory reduction to NH4+wasabsent. Conversely, respiratory N2O reduction wasdirectly coupled to N2fixation.